ADAPTASI DESAIN POSTER FILM SEBAGAI MEDIA PROMOSI DALAM PERSPEKTIF LINTAS BUDAYA DAN PEMASARAN GLOBAL - Roudlotul Jannati Rochnadia Noorva Yudhitya (Canthing, 2023)
For the audience, movie posters may only be one of the marketing agendas to promote a film. However, for production studios and distributors, film posters must be able to persuade viewers and arouse their curiosity or interest in watching the movie. Movie posters can also be seen as an insight into a certain culture in life. This study reviews the strategies of filmmakers with marketers in publishing their film posters for other countries. A literature study was chosen as a research method to reach more insight from various sources, as well as compare findings from previous research. The findings from this study indicate that film posters are not designed in one version globally for audiences around the world, but are redesigned and sometimes translated according to the local culture, thoughts, and aesthetics of the people of that country.Keywords: Design, Film Poster, Marketing, Cross-Culture, Promotion